Miniaturized dual-stub resonator of bandstop filter / Farawahida Ahmad Ramli - Ahmad Ramli, Farawahida (2011)
In this study, capacitor is proposed to tune the resonant frequency of dual-stub resonator of band stop filter to miniaturize the circuit size. The capacitors is attach to an open circuit dual-stub to tune the 2 GHz dual-stub resonant to lower frequency which is 1 GHz. A capacitor can store electric energy when disconnected from its charging circuit, so it can be used like a temporary battery using Advance Design System (ADS) 2009 software, a microstrip of dual-stub resonator of band stop filter has been designed. The stub length is V4 with the center frequency at 2 GHz. Simulation was done using ADS 2009 circuit simulator on the effect of adding capacitor to determine the frequency response of the band stop dual-stub resonator and the effect to the circuit size. Then, fabrication is done for dual stub resonator at 2 GHz with 3.3pF capacitor microstrip structure on the FR4 substrate. Measurement is done using Vector Network Analysis (VNA) to obtain the frequency response for Sn and S12 that will be compared with the simulation result. The layout dimension for 1 GHz dual-stub resonator is also compared with the dimension of 2 GHz dual-stub resonator. It is proven that capacitor can reduced frequency value of higher dual-stub resonator as well as the circuit size. As conclusion, the 2 GHz dual-stub resonator has achieved 50.2% circuit miniaturized compared to 1 GHz resonator dimension. It is suitable for processor and wireless network system applications.